2008
DOI: 10.1111/j.1365-313x.2008.03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functionally essential amino acid for Arabidopsis cyclic nucleotide gated ion channels using the chimeric AtCNGC11/12 gene

Abstract: We used the chimeric Arabidopsis cyclic nucleotide-gated ion channel AtCNGC11/12 to conduct a structurefunction study of plant cyclic nucleotide-gated ion channels (CNGCs). AtCNGC11/12 induces multiple pathogen resistance responses in the Arabidopsis mutant constitutive expresser of PR genes 22 (cpr22). A genetic screen for mutants that suppress cpr22-conferred phenotypes identified an intragenic mutant, #73, which has a glutamate to lysine substitution (E519K) at the beginning of the eighth b-sheet of the cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 53 publications
3
60
0
Order By: Relevance
“…Transient heterologous expression of chimeric At-CNGC11/12 in N. benthamiana triggers Ca 2+ -dependent spontaneous HR-like PCD, suggesting that CNGC11/12 is a constitutively active and/or misregulated form of CNGC12, which is a positive regulator of immunity (Baxter et al, 2008;Urquhart et al, 2007). Low temperature is known to enhance immune responses in plants (Hua, 2013), and shifting to lower temperature has been previously shown to enhance the PCD phenotype induced by CNGC11/12 mutants (Mosher et al, 2010;Chin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transient heterologous expression of chimeric At-CNGC11/12 in N. benthamiana triggers Ca 2+ -dependent spontaneous HR-like PCD, suggesting that CNGC11/12 is a constitutively active and/or misregulated form of CNGC12, which is a positive regulator of immunity (Baxter et al, 2008;Urquhart et al, 2007). Low temperature is known to enhance immune responses in plants (Hua, 2013), and shifting to lower temperature has been previously shown to enhance the PCD phenotype induced by CNGC11/12 mutants (Mosher et al, 2010;Chin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CNGC12 is a positive regulator of immunity (Moeder et al, 2011), and CNGC11/12 was hypothesized to represent a misregulated form of CNGC12 that constitutively induces autoimmune phenotypes including hypersensitive response (HR)-like programmed cell death (PCD) in a constitutive manner (Yoshioka et al, 2006;Urquhart et al, 2007;Baxter et al, 2008). Activation of such autoimmunity can be assessed via Agrobacterium tumefaciens-mediated transient expression of At-CNGC11/12 in Nicotiana benthamiana, where CNGC11/12-GFP, but not CNGC12-GFP, can induce PCD (Yoshioka et al, 2006).…”
Section: Loss Of Cam Binding To the Nt Site Triggers Cngc12-induced Pmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 It has been reported that the expression of AtCNGC11/12 and its channel activity is attributable for the cpr22 phenotype. 17,18 A genetic screen for mutants that suppress cpr22-conferred phenotypes identified over 20 novel mutant alleles in AtCNGC11/12. 1,18 These intragenic mutants are excellent tools to study the structure-function relationship of plant CNGCs.…”
Section: Calmodulin Binding To Arabidopsis Cyclic Nucleotide Gated Iomentioning
confidence: 99%